2018
DOI: 10.2334/josnusd.17-0381
|View full text |Cite
|
Sign up to set email alerts
|

New oral hygiene care regimen reduces postoperative oral bacteria count and number of days with elevated fever in ICU patients with esophageal cancer

Abstract: Using a controlled pre/post study design, we investigated the effects of professional mechanical cleaning of the oral cavity with benzethonium chloride, interdental brushes, and hydrogen peroxide on the number of oral bacteria and postoperative complications among esophageal cancer patients in an intensive care unit. Before surgery, 44 patients with esophageal cancer were recruited at Okayama Hospital from January through August 2015. The control group (n = 23) received routine oral hygiene care in the intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
(45 reference statements)
0
12
0
1
Order By: Relevance
“…A rapid bacterial detection apparatus (PHC Holdings Co., Ltd., Tokyo, Japan) that consisted of the elements necessary for dielectrophoretic impedance measurement (DEPIM) was used. 15 , 16 These elements included an electrode chip to capture bacteria, a cell-retaining sample solution, an alternating current circuit for dielectrophoresis, and an impedance measurement circuit. Measurement was initiated by placing the sample solution (approximately 5 mL) and electrode chip inside the device and pressing a button.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A rapid bacterial detection apparatus (PHC Holdings Co., Ltd., Tokyo, Japan) that consisted of the elements necessary for dielectrophoretic impedance measurement (DEPIM) was used. 15 , 16 These elements included an electrode chip to capture bacteria, a cell-retaining sample solution, an alternating current circuit for dielectrophoresis, and an impedance measurement circuit. Measurement was initiated by placing the sample solution (approximately 5 mL) and electrode chip inside the device and pressing a button.…”
Section: Methodsmentioning
confidence: 99%
“… 15 The collection pressure was about 21 g, and a 1-cm span was sampled by rubbing the swab back and forth three times. 16 …”
Section: Methodsmentioning
confidence: 99%
“…Sample size was estimated assuming a 1.0 Ă— 107 (SD, 1.3 Ă— 107) cfu/mL or greater reduction in the numbers of oral bacteria on the tongue in the intervention compared with the control group [16]. Based on the data, we determined that 28 inpatients per group would be necessary to provide 80% power with an alpha of 0.05 in two-tailed and unpaired t-tests.…”
Section: Methodsmentioning
confidence: 99%
“…Postoperative, professional oral hygiene care can reduce the number of oral bacteria on the tongue [16], the numbers of oropharyngeal bacteria [17], and complications such as pneumonia [18]. On the other hand, self-care as well as professional care are needed to improve postoperative oral hygiene status, which contributes to complications.…”
Section: Introductionmentioning
confidence: 99%
“…In hospitalized patients, infectious complications, such as ventilator-associated pneumonia (VAP) and surgical site infection, sometimes lead to critical conditions [4][5][6]. Some studies have suggested that oral care, including tongue cleaning, could reduce those complications, and that oral care improving the quality of patient care was economically viable [4][5][6]. Also, Tajima et al reported that tongue cleaning was also useful for elders fed with a feeding tube because it could decrease the number of microbes on the tongue surface [7].…”
Section: Introductionmentioning
confidence: 99%